State and Social-Centered Approaches to The Political Economy of South Korea - Miftah Farid; Riska Luneto (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2023)
This paper aims to analyze South Korea's development efforts by looking at the two differences between the state-centered and social-centered approaches. Both have different views from each other, but this is what the author tries to use to describe the process of South Korea's economic development during the Park Cung-Hee administration amidst the intervention of capitalist groups. Development is divided into three important phases; preconstruction, stabilization, and rapid development with a development strategy within a certain period of time and industrialization in many sectors. In the process, South Korea emphasizes the role of the government and other stakeholders who have a major role in the country's economic development, although in the midst of its development there are internal obstacles experienced by South Korea, South Korea actually shows its economic success today.